Spatial cognitive processes involved in electronic circuit interpretation and translation: their use as powerful pedagogical tools within an education scenario - Pule, Sarah; Attard, Jean-Paul (Design and Technology Education: An International Journal, 2021)
While there is much research concerning the interpretation of diagrams such as geographical maps and networks for information systems, there is very little on the diagrams involved in electrical and electronic engineering. Such research is important not only because it supports arguments made for other types of diagrams but also because it informs on the cognitive processes going on while learning electrical and electronic engineering domains, which are generally considered difficult to teach and learn. Such insight is useful to have as a pedagogical tool for teachers. It might also benefit would be self-learners, entrepreneurs, and hobbyists in the field because it can guide self-learning practices. When cognitive practices specific to this knowledge domain are more understood, they might give rise to automated intelligent tutor systems which could be used to augment teaching and learning practices in the education of electrical and electronic engineering. This research analyses the spatial cognitive processes involved in the translation of an electronic circuit schematic diagram into an iconic representation of the same circuit. The work shows that the cognitive affordances of proximity and paths perceived from a circuit schematic diagram have great influence on the design of an iconic diagram, or assembly diagram, representing a topologically equivalent electronic circuit. Such cognitive affordances reflect and affect thought and can be used as powerful pedagogical tools within an educational scenario.